Challenging the 'Native Speaker' Ideal: The Impact of Native Speakerism on Language Education - Dey, Manna; Amelia, Rizky; Herawati, Yayuk Widyastuti (English Department FBS UNP, 2023)
Native-Speakerism has emerged as a prominent element of contemporary TESOL discourse and a frequent talking point when it comes to issues of language-related prejudice and discrimination. It does so by building on a diverse range of sources and intentionally slanting toward amusing the trendy. It is suggested that the ideological conception of native-speakerism applies retroactively to the coveted victimization and the narrative of indignation that goes along with it to people who identify as